Synergistic operation strategy of electric-hydrogen charging station alliance based on differentiated characteristics - Zhang, Qian; Qin, Tianxi; Wu, Jiaqi; Hao, Ruiyi; Su, Xin; Li, Chunyan (Energy (Oxford), 2024)
Due to the rapid development of the automotive industry and the increasing shift towards cleaner energy, electric and hydrogen vehicles have great potential for growth. Therefore, charging stations need to transition from single charging forms to electric-hydrogen coupling charging. This paper focuses on the problem of mismatch between source and load in time and space when operating a Charging-Hydrogenation Composite Station (CHCS) independently. This leads to resource waste in the full-cycle and long-time sequence, making it difficult to achieve economic benefits. The characteristics that differentiate CHCS, such as geographic location, operating equipment, charging demand, and temporal attributes, are taken into account. CHCS in suburban, residential, tourist attractions, and industrial areas are modeled differently. Through improved Nash negotiation game modeling, a peer-to-peer (P2P) energy trading mechanism is established. The CHCS leverages its resource endowment advantages to ensure that each subject and the alliance as a whole can benefit through the coupled electricity-hydrogen energy trading. To ensure privacy in CHCS transactions, a distributed alternating direction method of multipliers (ADMM) algorithm is used to iteratively solve the problem and achieve a fair distribution based on the energy contribution size of each CHCS. Finally, simulation examples are used to verify the validity of the proposed model. The study shows that the electricity-hydrogen energy coupling trading strategy proposed in this paper can realize the synergistic mutual benefit of each CHCS, and in terms of economy, the overall benefit of the alliance has been improved by 7.58 %, and in terms of new energy consumption, the regional PV has gone from a consumption rate of 49.98 % to realize 100 % full consumption, and the wind power consumption rate has increased from 52.38 % to 96.34 %. •The coupled trading and revenue sharing of electric and hydrogen energy among multiple CHCSs.•The differentiation of temporal attributes, spatial geography, equipment types, and load characteristics are considered.•Implications of Nash negotiations and energy sharing on the CHCSs costs and consumption of new energy are investigated.•Distributed ADMM algorithms are used to solve the Nash bargaining problem.